Pendidikan Kepemimpinan Perspektif K.H. Imam Zarkasyi - Zuli Dwi Rahmawati (TA'LIM : Jurnal Studi Pendidikan Islam, 2019)
Education is very important for the development of life, improving the quality of life, both in terms of science, behavior, and uses in society, generally in the life of the nation and state. Therefore education must always be developed in accordance with the development and demands of the era, including Leadership Education. This is based on reality globally, nowadays the leadership of Muslims in the world is chaotic facing various trials and threats, the Islamic world is rocking due to the lack of satisfaction of their leaders. It is also intended that fitrah as a caliph in every human being can be functioned as it has been outlined by Allah in Islam. One of the efforts to improve the quality of cadres of leaders according to Islamic teachings is by reviewing and applying concepts that have been formulated by Kyai and education experts, as well as leadership that has been implemented by KH Imam Zarkasyi in his hut, so that his alumni have been active as leaders in this country. Recognizing the importance of KH Imam Zarkasyi leadership education which addresses leadership education in accordance with Islamic teachings, where on the one hand leadership is based on the Qur'anic Islamic values ​​and the Sunnah. From the results of this study, it can be seen that leadership education according to KH Imam Zarkasyi is based on the argument that humans are leaders who will be held accountable for their leadership. Whereas the function of the leader is to organize the totality of life, it requires a cadre regeneration institution that is deliberately formed to become an ideal place of life so that cadres will be formed and fostered a mindset, attitude and behavior as a leader by applying high discipline.